In vitro microsomal metabolism of some N-benzyl substituted tertiary amines in the rat [Farede bazi N-benzil substituenti tertiari aminlerin in vitro mikrozomal metabolizmasi] - (:unkn) unknown (My University, 1997)
The in vitro hepatic microsomal metabolism of three different substituted benzylic tertiary amines ie. N-isopropyl-N,N-dibenzylamine (PDBA), N-(2,4,6-trimethylbenzyl)-N,N-dibenzylamine (MDBA) and N-(2,6- dichlorobenzyl)-N,N-dibenzylamine (CDBA) was studied in the rat to establish whether N-oxidation and N-dealkylation reactions occured. Substrates and their potential metabolites ie. the corresponding N-oxides and secondary amines were synthesised. The structures of these compounds were confirmed by UV, IR, 1H-NMR and MASS spectroscopic techniques and their elemental analyses. Separation was achieved by thin layer chromatography (TLC) and high pressure liquid chromatography (HPLC). Substrates were incubated with the microsomes isolated from rat liver in the presence of co-factors including NADPH. Substrates and metabolites were then extracted from biological systems with dichlromethane. Metabolites occured were compared with their authentic standards and the metabolic pathways were clarified. Oxidative dealkylation leading to the formation of the corresponding secondary amines and aldehydes were detected as major routes of metabolism for these there substrates. However, no N-oxide metabolites were detected.
Keywords: Benzylic tertiary amines; In vitro metabolism; Microsomes